DETOKS KEUANGAN RUMAH TANGGA : TERAPI AKUNTANSI SEDERHANA UNTUK MENGATASI KANKER (KANTONG KERING) PASCA –LEBARAN ATAU LIBURAN - Femba Akris Diantoro; Khurin'in Ratnasari; Muhammad Hamdi; Dovi Iwan Musthofa Habibillah (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2026)
Household financial distress following high-consumption periods such as holidays remains a recurring issue in Indonesia, including among the PKK community in Jombang Village. This condition is primarily driven by limited practical accounting literacy in managing cash flows, leading to a dependency on consumptive debt. This community service program aimed to improve the financial health of partners through a structured financial management intervention. The method employed was Participatory Action Research (PAR), consisting of four stages: financial diagnosis, digital-based recording implementation, continuous monitoring, and evaluation. The results showed a 154% increase in average financial literacy scores, with the most significant improvement in digital recording discipline, which rose by 360%. Furthermore, the implementation of the 50/30/20 budgeting method reduced non-essential expenditures by 25% and shifted partners' cash flow from deficit to surplus within 30 days. These findings suggest that the digitalization of simple financial records can serve as an effective strategy for fostering behavioral change and strengthening household financial resilience.